Phase-Dependency of Medial-Lateral Balance Responses to Sensory Perturbations During Walking - Reimann, Hendrik; Fettrow, Tyler; Grenet, David; Thompson, Elizabeth D.; Jeka, John J. (Frontiers in Sports and Active Living, 2019)
The human body is mechanically unstable during walking. Maintainingupright stability requires constant regulation of muscle force by the centralnervous system to push against the ground and move the body mass in thedesired way. Activation of muscles in the lower body in response to sensoryor mechanical perturbations during walking is usually highly phase-dependent,because the effect any specific muscle force has on the body movement dependsupon the body configuration. Yet the resulting movement patterns of theupper body after the same perturbations are largely phase-independent. Thisis puzzling, because any change of upper-body movement must be generated byparts of the lower body pushing against the ground. How do phase-dependentmuscle activation patterns along the lower body generate phase-independentmovement patterns of the upper body? We hypothesize that when a sensorysystem detects a deviation of the body in space from a desired state thatindicates the onset of a fall, the nervous system generates a functional responseby pushing against the ground in any way possible with the current bodyconfiguration. This predicts that the changes in the ground reaction forcepatterns following a balance perturbation should be phase-independent. Herewe test this hypothesis by disturbing upright balance in the frontal plane using Galvanic vestibular stimulation at three different points in the gait cycle. Wemeasure the resulting changes in whole-body center of mass movement and thelocation of the center of pressure of the ground reaction force. We find that themagnitude of the initial center of pressure shift in the direction of the perceived